Multiparadigmatic approach in organization studies: developments and limitations - Amboni, Nério; Caminha, Daniel Ouriques; Andrade, Rui Otávio Bernardes de; Fernandes, Maurício (Revista de Administração da UFSM, 2017)
This paper aims to discuss the developments and limitations of multiparadigmatic approach to developing organizational studies. The model of the four paradigms (functionalist, interpretive, radical humanist and radical structuralist) proposed by Burrell and Morgan (1979) accelerated the proliferation of competing perspectives, besides generating the polarization and segregation. Each paradigm is treated in a unique perspective and therefore incommensurable with another paradigm, against the scholars who defend the communication between paradigms. The pluralistic view is relevant because it encourages scholars to see organizations in different prisms to succumb to the reductionist view of the theory of organizations, and encourage the development of new perspectives for organizational analysis. However, the use of multiple paradigms also presents limits, since the researcher when dealing with different approaches can be without reference or justification, besides sometimes having difficulty to be away from the dominant paradigm. All these joints and paradigmatic joints can be made, provided that the researcher always has a reference and a basis, in order to maintain the coherence and the consistency of what is being researched.